1996
DOI: 10.2355/isijinternational.36.563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Band Annealing Temperature on the Magnetic Properties of Low-carbon Electrical Steels.

Abstract: The effect of hot band annealing temperature, range from 700-1 OOO'C, on the magnetic properties of low-carbon electrical steels measuredat 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The prior hot band grain size also influences the final grain size after final continuous annealing. 17) During final annealing, the prior grain boundary is a potential nucleation site for recrystallization. Fewer nucleation sites occurring in the deformed matrix lead to a coarser grain.…”
Section: Grain Size After Final Cold-rolled Steel Sheetsmentioning
confidence: 99%
“…The prior hot band grain size also influences the final grain size after final continuous annealing. 17) During final annealing, the prior grain boundary is a potential nucleation site for recrystallization. Fewer nucleation sites occurring in the deformed matrix lead to a coarser grain.…”
Section: Grain Size After Final Cold-rolled Steel Sheetsmentioning
confidence: 99%
“…Electrical steel texture development has been investigated [1][2][3][4][5][6][7][8][9] and the effect of the hot band grain size has been the subject of several studies. [6][7][8] But, more specifically, the effect of silicon on the texture development of semiprocessed electrical steels was not studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] But, more specifically, the effect of silicon on the texture development of semiprocessed electrical steels was not studied in depth. Among the reports on this subject are those of Kestens et al 1) that discussed the recrystallization texture in high Si steels and Hou,2) which found more favorable recrystallization textures for steels with higher Si content.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative processing routes have been reported for production of low core losses electrical steel grades, such as optimized hot rolling, annealing prior to cold rolling and cold rolling in two steps with intermediate annealing [18,19]. Annealing prior to cold rolling has been investigated mainly in ultra-low carbon electrical steels [20,21]. Hou [20] studied the effect of annealing prior to cold rolling on the energy losses of an electrical steel containing 0.0023% C, 0.31% Si and 0.002% Al.…”
Section: Introductionmentioning
confidence: 99%
“…Annealing prior to cold rolling has been investigated mainly in ultra-low carbon electrical steels [20,21]. Hou [20] studied the effect of annealing prior to cold rolling on the energy losses of an electrical steel containing 0.0023% C, 0.31% Si and 0.002% Al. It was observed that annealing prior to cold rolling promoted an increase of the (I/I R ) 110 and (I/I R ) 200 relative pole densities and a decrease of the (I/I R ) 211 and (I/I R ) 222 during the final annealing.…”
Section: Introductionmentioning
confidence: 99%